Exposure to chronic hypoxia induces qualitative changes of collagen in the walls of peripheral pulmonary arteries - Novotná, J; Herget, J (Life sciences, 1998)
Qualitative changes of vascular wall matrix collagens in chronic hypoxic pulmonary hypertension were studied by gel electrophoresis. Male adult rats (n = 12) were exposed to hypoxia (FiO2 = 0.1, 3 wks). Control rats (n = 13) were kept in air. Samples of peripheral pulmonary arteries (PPA, diam. 100-400 microm), main branches of pulmonary artery, and aorta were dissected. Arterial samples were treated with 4M guanidine-HCl to remove noncollagenous moieties and the collagenous stroma was dissolved by limited pepsin digestion at low pH. Low molecular mass peptides (M. W. approx. 76 and 66 kD) were detected in the gel electrophoretic profile of collagen peptides of PPA of the chronically hypoxic animals and in aorta of both hypoxic and normoxic groups. These peptides were absent in the PPA of normoxic rats. Since the 76 kD peptide bound anticollagen type I antibodies, it appears to be of collagenous nature and it may be the result of collagenolytic activity in PPA isolated from hypoxic lungs. This was confirmed by zymography. We conclude that exposure of rats to chronic hypoxia results in the presence of low molecular mass peptides in the wall matrix of PPA which resemble those found in aorta of normoxic animals. Collagenolytic activity in the walls of peripheral pulmonary arteries may participate in the mechanism of lung vascular remodelling in chronic hypoxia.
Keywords: kolagen; elektroforéza v polyakrylamidovém gelu; Rats; hypoxie; Hypoxia; arteria pulmonalis; Collagen; Aorta; Rats, Wistar; mužské pohlaví; aorta; krysa rodu Rattus; Body Weight; Pulmonary Artery; Electrophoresis, Polyacrylamide Gel; zvířata; tělesná hmotnost; potkani Wistar; Male; Animals